Capacity Reduction for Urban Road Due to Curbside Bus Stop: A Case Study of Srijana Chowk, Nepal - Thapa, Suraj; Tiwari, Hemant; Joshi, Madhav (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.008 Curbside bus stops have a significant impact on traffic characteristics, including speed and roadway capacity. Srijana Chowk, the urban area within Pokhara metropolitan city, was selected for the study. The objective of the study is to evaluate the reduction in roadway capacity at the curbside bus stop at Srijana Chowk. The primary data was collected using videographic techniques. The analysis indicated that Srijana Chowk’s curbside bus stop caused an average stream speed reduction of 6.23%. The capacity at the Srijana Chowk bus stop was 2532 PCU/hr and 2718 PCU/hr at the curbside and on the opposite side of the bus stop, respectively. Similarly, the capacity reduction was analyzed to be 16.62% and 6.84% by the Indonesian Highway Capacity Manual and Greenshield’s model, respectively.